The concept of self-education and its part in training future specialists - Sagimbaev, A.A.; Esengulov, Zh.K.; Bodikov, S. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
This article considers one of the main practical tasks of pedagogical science of the Republic of Kazakhstan at the present stage and the problems of formation of the creative person, disclosure of natural potential, also formation and creations of conditions for her realization. Authors showed ways of comprehensive training of experts and development of creative thinking of students by means of their activization through independent work. In the course of the research of the specified subject authors used the modern pedagogical technologies directed to activization and improvement of activity of students in independent education. Proceeding from it, the organization by management of independent training of students is based on the checked by authors, technological approach. And therefore it is very necessary to develop production in the conditions of present realities. Problems of statement of tasks in receiving systematic education are allocated. Authors made decisions if education serves ensuring the general development of future expert, then the purpose of independent education is formation of professionalism and increase in his skill. Therefore, certainly, in the course of study, it is necessary to direct students to receiving independent education correctly.
Болашақ мамандарды дайындаудағы өзіндік білім алудың тұжырымдамасы жəне оның рөлі
Концепция самообразования и его роль в подготовке будущих специалистов
Keywords: pedagogics; psychology; visual art; creative thinking; self-education; drawings; methods of teaching; conceptual model; complex process; future specialists